Microbiology in Action. - Heritage, John (Studies in biology., 1999)
Microbes have an impact on our everyday lives, from the food we eat and the water we drink to the multitude of human infections. The authors introduce both the beneficial and adverse effects of interactions between microbes and their environment in a manner accessible to the non-specialist.